Prognostic value of Bcl-2 in breast cancer patients treated with neoadjuvant anthracycline based chemotherapy - Vargas Roig, Laura Maria (2008)
We have analyzed the predictive/prognostic value of Bcl-2 protein in breast cancer patients treated with neoadjuvant chemotherapy. One hundred and ten patients were submitted to two different chemotherapeutic regimens: a) 5-fluorouracil, adriamycin or epirubicin, and cyclophosphamide (FAC/FEC) during 2-6 cycles before surgery and 3 or 4 additional cycles of FAC/FEC after surgery (n = 40) and b) doxorubicin (D) 75 mg/m2 or epirubicin (E) 120 mg/m2 during 4 cycles before surgery, and 6 cycles of cyclophosphamide, methotrexate, and 5-fluorouracil (CMF) after surgery (n = 70). Bcl-2 expression, evaluated by immunohistochemistry, did not change significantly after chemotherapy and was not related to clinical/pathological response. In FAC/FEC group, Bcl-2 positive expression after chemotherapy correlated with better disease free survival (DFS) and overall survival (OS) (P = 0.008 and P = 0.001). In D/E group, Bcl-2 also correlated with better DFS and OS (P = 0.03 and P = 0.054) in the post-chemotherapy biopsies. An unusual nuclear localization of Bax was observed in some biopsies, but this localization did not correlate with the tumor response or outcome of the patients. We found that a high Bcl-2 expression had no predictive value but had prognostic value in breast cancer patients treated with neoadjuvant anthracycline based chemotherapy.